Challenges of newspaper reportage of the Niger Delta conflict: reporter’s perspectives of the insurgency - Ofem O.O. (Asian Journal of Media and Communication, 2018)
The paper assessed the viewpoints of reporters on the challenges of newspaper reportage of the Niger Delta conflict in Nigeria (2006-2007). The Guardian, The Vanguard and The Niger Delta Newspapers were purposively selected for the study due to both their national and local outlooks in the coverage and reportage of the conflict. In-depth interviews were conducted on two (2) correspondents each from the three (3) selected newspapers making a total of six (6), while four (4) respondents from each of the newspaper making 12 were selected for questionnaire administration. Results obtained identified ownership (41.7%) and media protective interest (33.3%) as the primary challenges faced by the media in the reportage of the Niger Delta conflict. The actions of the Ijaw Youths, militant activities (41.7%), killings (25%) and hostage taking (16.6%) considerably affected the nature of reportage during the heat days or periods of the conflict. Findings from the in-depth interviews showed that the geology (nature of terrain) of the conflict area, issue of trust from the militants and security forces exerted considerable influence on the selected newspapers failure to perform the required effective mediation and intervention role in the conflict.